1970 SONRASI TÜRKİYE’DEKİ İSLAMCILAR VE DEMOKRASİ: ŞİRKTEN SAHİPLENMEYE PARADİGMA DEĞİŞİMİNİN İZ SÜRÜMÜ - Koyuncu, Ahmet Ayhan (My University, 2015)
İslamcılık ve demokrasi arasındaki ilişki, İslamcılığın 150 yıllık tarihi boyunca çeşitli biçimlerde gelişmiştir. Aslında İslamcılık dendiğinde tekil bir hareket söz konusu değildir. Türkiye'de İslamcılığın genel olarak beş farklı döneminde söz edilebilir. Dönemlere göre farklı nitelikler arz eden İslamcılık, 1970 sonrasında önemli bir değişim geçirmiş ve önceki dönemlerden siyasallık vurgusu ile ayrışmıştır. Yaşanan bu değişim, İslamcılığın tarihsel sürecinde ele aldığı pek çok konuya da farklı bir bakış açısı getirmiştir. Devlet, toplum, ekonomi, siyaset vs. pek çok konu, 1970 sonrasında oldukça farklı bir çerçevede değerlendirilmiştir. Demokrasi konusu bu süreçte önceki İslamcılardan farklı bir çerçevede ele alınmış ve demokratik yönetimler, Allah'ın egemenliğini insana veren bir şirk rejimleri olarak tanımlamaya başlanmıştır. Ancak süreç içerisinde demokrasiye ilişkin bakış açısı değişmeye başlamıştır. Bugün İslamcıların demokrasiye bakışlarında önemli bir değişim söz konusudur. 1997 de gerçekleşen 28 Şubat darbesi ve akabinde Adalet ve Kalkınma Partisi'nin iktidara gelmesi, İslamcılar ile demokrasi arasında sıcak bir ilişkinin kurulmasına sebep olmuş ve bugün İslamcılar adeta demokrasiyi sahiplenmeye başlamışlardır. Bu noktada çalışma, yaşanan bu büyük değişimi anlamaya ve bu değişime neden olan faktörleri irdelemeyi hedeflemektedir. Görülen en büyük değişim ise demokrasiyi anlama biçiminde yatmaktadır. İslamcılar, demokrasi konusunu iki biçimde algılamıştır: Birincisi bir rejim olarak demokrasi, ikincisi ise bir yönetim mekanizması olarak demokrasi. Yaşanan bu algı değişimi, İslamcıların demokrasiyle kurduğu ilişkinin bugünkü noktaya gelmesini anlaşılabilir kılmaktadır

The relation between Islamism and democracy has improved various forms since 150 years. Indeed, there is no unique Islamism or Islamist movement. Many different movements from each other define under the concept of Islamism. Islamism in Turkey can separate five periods in general. The first period is the late Ottoman era: between 1850 and 1924. This period also called Ottoman’s Islamism. The second period starts with the foundation of Republic of Turkey and finishes in 1950. We can say for this period that interregnum of Islamism. The third period of Islamism in Turkey is the years between 1950 and 1970. In these years, Islamism had owned rightist, statist, and nationalist reflexes. The fourth period of Islamism is the years between 1970 and 1997. This period’s Islamism can be named pure Islamism or political Islamism and thus it has a powerful political emphasis. The fifth and last period of Islamism has started with the February 28 coup in 1997 and it still goes on. Islamism, exhibiting different characteristics according to the period, has undergone significant changes after 1970. Different from its previous period, Islamism has turned into a movement highlighting tawhid and emphasizing political dimensions. This changing started along with translating some texts from Islamic movements’ and their leaders in other countries like Egypt and Pakistan to Turkish in 1960s and 1970s. Islamists has brought different perspectives in a lot of topics such as state, society, economy, politics etc. These issues have been evaluated in a quite different context of post-1970. For instance, the perception of state has undergone a radically change during this period. Previous Islamists was owned the state. But for the latter Islamist, state is defined as a disbelievers (kafir) formation which should be islamization. An Islamic state definition is made and it was described in detail that how it should be. With state issues, democracy issues also were discussed in a different context from the previous Islamists in the process and democratic governments have begun to describe as a shirk regime (polytheism) that the sovereignty belongs to Allah gives people. But the outlook for democracy has started to change in the process. In fact, discussions about democracy between Islamists have shaped in two different definitions. The first group’s definition of democracy is a way of life or an ideology or a philosophy of life. The Group who see democracy as incompatible with Islam prefers this definitions. The second definition is that democracy is a management mechanism independent from ideology. According to this approach, democracy is a tool that can be used as a means to an Islamic government. Especially after 1980s, this second definition related to democracy began to embrace in Islamists. In fact, democracy is quite a controversial issue in itself. There is no only one definition of democracy. If we seek the literature of democracy, we can see a lot of its definitions, models and applications. Moreover, current The relation between Islamism and democracy has improved various forms since 150 years. Indeed, there is no unique Islamism or Islamist movement. Many different movements from each other define under the concept of Islamism. Islamism in Turkey can separate five periods in general. The first period is the late Ottoman era: between 1850 and 1924. This period also called Ottoman’s Islamism. The second period starts with the foundation of Republic of Turkey and finishes in 1950. We can say for this period that interregnum of Islamism. The third period of Islamism in Turkey is the years between 1950 and 1970. In these years, Islamism had owned rightist, statist, and nationalist reflexes. The fourth period of Islamism is the years between 1970 and 1997. This period’s Islamism can be named pure Islamism or political Islamism and thus it has a powerful political emphasis. The fifth and last period of Islamism has started with the February 28 coup in 1997 and it still goes on. Islamism, exhibiting different characteristics according to the period, has undergone significant changes after 1970. Different from its previous period, Islamism has turned into a movement highlighting tawhid and emphasizing political dimensions. This changing started along with translating some texts from Islamic movements’ and their leaders in other countries like Egypt and Pakistan to Turkish in 1960s and 1970s. Islamists has brought different perspectives in a lot of topics such as state, society, economy, politics etc. These issues have been evaluated in a quite different context of post-1970. For instance, the perception of state has undergone a radically change during this period. Previous Islamists was owned the state. But for the latter Islamist, state is defined as a disbelievers (kafir) formation which should be islamization. An Islamic state definition is made and it was described in detail that how it should be. With state issues, democracy issues also were discussed in a different context from the previous Islamists in the process and democratic governments have begun to describe as a shirk regime (polytheism) that the sovereignty belongs to Allah gives people. But the outlook for democracy has started to change in the process. In fact, discussions about democracy between Islamists have shaped in two different definitions. The first group’s definition of democracy is a way of life or an ideology or a philosophy of life. The Group who see democracy as incompatible with Islam prefers this definitions. The second definition is that democracy is a management mechanism independent from ideology. According to this approach, democracy is a tool that can be used as a means to an Islamic government. Especially after 1980s, this second definition related to democracy began to embrace in Islamists. In fact, democracy is quite a controversial issue in itself. There is no only one definition of democracy. If we seek the literature of democracy, we can see a lot of its definitions, models and applications. Moreover, current The relation between Islamism and democracy has improved various forms since 150 years. Indeed, there is no unique Islamism or Islamist movement. Many different movements from each other define under the concept of Islamism. Islamism in Turkey can separate five periods in general. The first period is the late Ottoman era: between 1850 and 1924. This period also called Ottoman’s Islamism. The second period starts with the foundation of Republic of Turkey and finishes in 1950. We can say for this period that interregnum of Islamism. The third period of Islamism in Turkey is the years between 1950 and 1970. In these years, Islamism had owned rightist, statist, and nationalist reflexes. The fourth period of Islamism is the years between 1970 and 1997. This period’s Islamism can be named pure Islamism or political Islamism and thus it has a powerful political emphasis. The fifth and last period of Islamism has started with the February 28 coup in 1997 and it still goes on. Islamism, exhibiting different characteristics according to the period, has undergone significant changes after 1970. Different from its previous period, Islamism has turned into a movement highlighting tawhid and emphasizing political dimensions. This changing started along with translating some texts from Islamic movements’ and their leaders in other countries like Egypt and Pakistan to Turkish in 1960s and 1970s. Islamists has brought different perspectives in a lot of topics such as state, society, economy, politics etc. These issues have been evaluated in a quite different context of post-1970. For instance, the perception of state has undergone a radically change during this period. Previous Islamists was owned the state. But for the latter Islamist, state is defined as a disbelievers (kafir) formation which should be islamization. An Islamic state definition is made and it was described in detail that how it should be. With state issues, democracy issues also were discussed in a different context from the previous Islamists in the process and democratic governments have begun to describe as a shirk regime (polytheism) that the sovereignty belongs to Allah gives people. But the outlook for democracy has started to change in the process. In fact, discussions about democracy between Islamists have shaped in two different definitions. The first group’s definition of democracy is a way of life or an ideology or a philosophy of life. The Group who see democracy as incompatible with Islam prefers this definitions. The second definition is that democracy is a management mechanism independent from ideology. According to this approach, democracy is a tool that can be used as a means to an Islamic government. Especially after 1980s, this second definition related to democracy began to embrace in Islamists. In fact, democracy is quite a controversial issue in itself. There is no only one definition of democracy. If we seek the literature of democracy, we can see a lot of its definitions, models and applications. Moreover, current The relation between Islamism and democracy has improved various forms since 150 years. Indeed, there is no unique Islamism or Islamist movement. Many different movements from each other define under the concept of Islamism. Islamism in Turkey can separate five periods in general. The first period is the late Ottoman era: between 1850 and 1924. This period also called Ottoman’s Islamism. The second period starts with the foundation of Republic of Turkey and finishes in 1950. We can say for this period that interregnum of Islamism. The third period of Islamism in Turkey is the years between 1950 and 1970. In these years, Islamism had owned rightist, statist, and nationalist reflexes. The fourth period of Islamism is the years between 1970 and 1997. This period’s Islamism can be named pure Islamism or political Islamism and thus it has a powerful political emphasis. The fifth and last period of Islamism has started with the February 28 coup in 1997 and it still goes on. Islamism, exhibiting different characteristics according to the period, has undergone significant changes after 1970. Different from its previous period, Islamism has turned into a movement highlighting tawhid and emphasizing political dimensions. This changing started along with translating some texts from Islamic movements’ and their leaders in other countries like Egypt and Pakistan to Turkish in 1960s and 1970s. Islamists has brought different perspectives in a lot of topics such as state, society, economy, politics etc. These issues have been evaluated in a quite different context of post-1970. For instance, the perception of state has undergone a radically change during this period. Previous Islamists was owned the state. But for the latter Islamist, state is defined as a disbelievers (kafir) formation which should be islamization. An Islamic state definition is made and it was described in detail that how it should be. With state issues, democracy issues also were discussed in a different context from the previous Islamists in the process and democratic governments have begun to describe as a shirk regime (polytheism) that the sovereignty belongs to Allah gives people. But the outlook for democracy has started to change in the process. In fact, discussions about democracy between Islamists have shaped in two different definitions. The first group’s definition of democracy is a way of life or an ideology or a philosophy of life. The Group who see democracy as incompatible with Islam prefers this definitions. The second definition is that democracy is a management mechanism independent from ideology. According to this approach, democracy is a tool that can be used as a means to an Islamic government. Especially after 1980s, this second definition related to democracy began to embrace in Islamists. In fact, democracy is quite a controversial issue in itself. There is no only one definition of democracy. If we seek the literature of democracy, we can see a lot of its definitions, models and applications. Moreover, current practices related to democracy have criticized and it has found a widespread debate in the search for new models recently. But for Islamists, these broad debates about democracy literature have taken into brackets and neglected. They have been moving out only these two definitions of democracy. The Islamists view for democracy can be summarized in three manners from the 1970s until today. On first manner, democracy takes away the sovereignty of God and gives to human. For Islam, this means polytheism that is, to ascribe partners to Allah. So, from this perspective, democracy is full of opposite of Islam and a Muslim cannot give confirmation to democracy. The Second manner refers to a point of view not as hard as the previous approach to democracy. They do not believe in democracy as a principle or as an ideal form of government. But they think that democracy is a tool for reaching the ideal form of Islamic rule. The third approach is ownership of democracy but this situation doesn’t reflect to Islamist discourse clearly. This discourse of democracy has constituted after February 28 process to struggle for existence. Today, there is a significant change the perception of democracy in Islamists. February 28 coup and the subsequently coming to power of the Justice and Development Party led to the establishment of a warm relationship between democracy and Islamists. Islamists have begun to embrace nearly democracy today. After the coup of February 28, democracy has been an existential ground for Islamists. From this point, the coup did not reduce the belief in democracy for Islamist; on the contrary, it increased. However, this ownership to democracy begun to bring some important problems for Islamist. Islamists have begun to lose their very lively thought climate especially in 1990s and they have faced with the danger of losing their claims to offer an alternative from their original source. At this point, the article aims to understand chancing in Islamists in particular of democracy. it appears that the biggest change lies on to understand of democracy.
ISLAMISTS IN TURKEY AFTER 1970 AND DEMOCRACY: THE TRACE OF CHANGING PARADIGM FROM SHIRK (POLYTHEISM) TO OWNERSHIP